MetaKosovo: Local and International Narratives. (February 2016) - Musliu, Vjosa; Orbie, Jan
This article: Problematizes the concept of 'home' and 'hospitality' in the case of unfinished states in terms of sovereignty. Argues that the concept of home is always preconditioned by the differences of host and guest; in cases where these two are intermingled/confused/unclear, the concept of home changes too. Looks at local and international narratives on Kosovo as a struggle of conceptual ownerships. Asserts that international and local narratives are always already both subject and object, yet fully neither at the same time, they exist and are destroyed by their own, and their subjectivity therefore lies in their autoimmunity, which makes them intrinsically undecidable. States that the Serbs and the Albanians have reached a historical point on their claim on Kosovo, where they share Kosovo as a state beyond 'home' (beyond sovereignty); for the Serbs, Kosovo as their previous 'home' is beyond remedy, for the Albanians Kosovo as their new/legitimate 'home' is beyond reach. This article examines local narratives on Kosovo and their role in crafting and articulating interpretations of Kosovo and international missions. Using the concept of 'home', as used and conceptualised by Jacques Derrida, the article reverses the order of who is 'guest' and 'host' in Kosovo and how that defines the local narratives on the subject. In the first part, attention is paid solely to letting local narratives deconstruct themselves, while in the second part we let them deconstruct the international narrative on Kosovo. The aim of the article is to present Kosovo as a battleground of division and commonality among the narratives and at the same time as an 'impossible' 'home' of all its narratives. In conclusion, some thoughts pave the way for the idea of 'renegotiating' the concept of 'home' with particular focus on 'home' in interventions and missions and its ultimate influence on the ethics of intervention .